2011
DOI: 10.25011/cim.v34i3.15185
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum cortisol levels with parameters of metabolic syndrome in men and women

Abstract: Association of serum cortisol levels with parameters of metabolic syndrome in men and women Abstract Purpose: Central fat distribution is signi cantly associated with an increased cortisol levels. We hypothesized that men with metabolic syndrome have a higher serum cortisol levels compared to women. e purpose of this study was to compare serum cortisol levels, and its correlation with serum leptin levels, between men and women with and without metabolic syndrome.Methods: A cross sectional study was performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…There are studies that have shown that patients with MS have higher circulating concentrations of cortisol, but there are also studies that have failed to find this relationship [10,11]. To our knowledge there are no studies that have measured serum cortisol concentrations in horses diagnosed with EMS, and the question remains whether horses with EMS differ in cortisol concentration compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that have shown that patients with MS have higher circulating concentrations of cortisol, but there are also studies that have failed to find this relationship [10,11]. To our knowledge there are no studies that have measured serum cortisol concentrations in horses diagnosed with EMS, and the question remains whether horses with EMS differ in cortisol concentration compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…In a Korean study, cortisol levels were not associated with MetS in women after adjustment for socioeconomic status, smoking, alcohol drinking, and daily physical activity [15]. Similarly, in an Iranian case-control study of adult patients with MetS from a diabetes clinic and healthy controls, the cortisol levels of controls did not differ significantly from those of MetS cases after multiple adjustments [14].…”
Section: Discussionmentioning
confidence: 89%
“…This lack of association ▶Table 1 General characteristics of cases of metabolic syndrome (MetS) and matched controls in female shift workers (n = 250), Southern Brazil, 2011. considered different cortisol parameters than we did. Some studies used the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) criteria for MetS [12][13][14] and/or having received medical treatment for diabetes, hypertension, or elevated triglycerides [12], whereas others used NCEP-ATP III Asian guidelines [15]. These studies considered various salivary cortisol measures: including measures over 3 days [13], 24-h urine cortisol excretion, bedtime salivary cortisol and the 1 mg dexamethasone suppression test [12], and fasting plasma cortisol [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a number of reports (19,22,25) HSD1 in obese subjects (29,30). Together with excess glucocorticoid secretion by the HPA axis (through increased peripheral glucocorticoidal signalling and cortisol reactivation) this may contribute to higher cortisol level observed in MetS.…”
Section: Endocrine Factors and Metsmentioning
confidence: 99%